1992
DOI: 10.1021/ja00044a043
|View full text |Cite
|
Sign up to set email alerts
|

Homologation of olefins with methane on transition metals

Abstract: it possible to take a set of generic skeletal force constants and use these for deriving structures with acceptable accuracy. As we have shown, the skeletal force constants are not generally transferable. If, however, one only wishes to obtain good structures of linear metallocenes, these force constants can be obtained for the metals in Table VI11 by simply using those of ferrocene as a generic set, provided the correct equilibrium bond lengths and angles are used. This will probably apply even for somewhat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 3 publications
1
27
0
2
Order By: Relevance
“…Van Santen and co-workers also demonstrated that the homologation of olefins (C 2 H 4 , C 3 H 6 , C 2 H 2 , etc.) with methane could occur over Ru/SiO 2 and Co/SiO 2 catalysts [15].…”
Section: Direct Conversion Of Ch 4 Under Nonoxidative Conditions: a Bmentioning
confidence: 97%
“…Van Santen and co-workers also demonstrated that the homologation of olefins (C 2 H 4 , C 3 H 6 , C 2 H 2 , etc.) with methane could occur over Ru/SiO 2 and Co/SiO 2 catalysts [15].…”
Section: Direct Conversion Of Ch 4 Under Nonoxidative Conditions: a Bmentioning
confidence: 97%
“…Labeled CO is then used in a two-step alkene homologation reaction previously developed in this laboratory [39]. 11 CO is pulsed over a vanadiumpromoted Ru/SiO2 catalyst at 350°C.…”
Section: Position (Mm)mentioning
confidence: 99%
“…The mixture was stirred for 24 hours, and the toluene removed under vacuum to produce the reconstituted fullerene soot.…”
Section: Reconstituted Fullerene Sootmentioning
confidence: 99%